Pyrolysis of typical MSW components by Py-GC/MS and TG-FTIR. (1st September 2019) - Ma, Wenchao; Rajput, Gulzeb; Pan, Minhui; Lin, Fawei; Zhong, Lei; Chen, Guanyi
Highlights: Interactions between different MSW components were studied. The strong interaction between PVC and vegetables was noticed. PVC in mixture promoted low pyrolysis temperature and fast conversion peaks. Paperboard has strong interaction with sawdust and cotton clothes. The kinetic approach was employed for the determination of activation energy. Abstract: Typical five MSW components (paperboard, PVC, sawdust, cotton fabric, and vegetables) were examined by using Py-GC/MS and TG-FTIR. Py-GC/MS experimental results showed different products at 500 °C with varying percentage including benzene derivatives, phenolic compounds, acids, alcohols, aldehydes and ketones, alkanes, and other compounds and revealed that the pyrolyzed organic content in different components varied by the temperature gradient. During rapid pyrolysis of PVC at 600–800 °C, the yield of major plasticized pyrolysis products including benzene and toluene was significantly increased from 21.76 wt% to 39.45 wt% and 15.03 wt% to 22.33 wt%, respectively. The thermogravimetric analysis also revealed the degradation and significant conversion of components at higher temperatures. Furthermore, to have a better understanding, mixed waste pyrolysis results were also compared with the calculated mixed waste results. The results disclosed the strong interactions between the PVC pipe and vegetables. In addition, the binary mixture of PVC with other components also promoted low-temperature pyrolysis. Besides, paperboard also showed strong interaction with sawdust and cotton clothes. TG-FTIR results disclosed that when the chemical composition and constituents of waste components are similar, the composition becomes the main influencing factor for mixed pyrolysis. In addition, a kinetic approach was also employed to determine the activation energy of MSW components during pyrolysis and the activation energy of the pyrolysis of vegetables was found to be in lower range with 82.85 E/(kJ·mol −1 ) in comparison with other components.